Engenharia de hibernação e o método Bow Tie: melhoria na gestão de riscos para maior integridade de um sistema de pull in/out - Gomes da Silva, Juliano; de Oliveira Barros, Carlos Frederico (Latin American Journal of Energy Research, 2024)
Integrity risks are present throughout the life cycle of an asset, including when in a temporary deactivation regime, called hibernation. In this study, it was found that during the hibernation of a pull in/out winch, used for connection/disconnection of offshore oil lines, there were failures in the management of integrity risks, which led to loss of profit, environmental impact and injury. Thus, the objective was to structure, in the light of the Bow Tie methodology, barriers to degradation in order to improve integrity for future operations. To this end, a qualitative approach was adopted based on literature review, field and documentary survey, in addition to the techniques of APR (Preliminary Risk Analysis), Risk Matrix and AAF (Failure Analysis Tree) to help the collection and analysis of data for the construction of the Bow Tie diagram. The Soft DSR (Soft Design Science Research) method proved to be adequate for the stages of this methodological approach. The result was a more robust degradation risk management, based on the solution consolidated in a Bow Tie diagram and an action plan, structured in 15 preventive barriers and 14 mitigation/recovery barriers, with reflections on safety and equipment readiness.